2003
DOI: 10.1021/es0258069
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Weight Characteristics of Humic Substances from Different Environments As Determined by Size Exclusion Chromatography and Their Statistical Evaluation

Abstract: Recorded molecular weights (MWs) for humic substances (HS) range from a few hundred to millions of daltons. For purposes of defining HS as a specific class of chemical compounds, it is of particular importance to ascertain if this broad range of MWs can be attributed to actual variability in molecular properties or is simply an artifact of the analytical techniques used to characterize HS. The main objectives of this study were (1)to establish if a preferential range of MWs exists for HS and (2) to determine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
127
2
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(143 citation statements)
references
References 21 publications
12
127
2
2
Order By: Relevance
“…SEC characterization of complex multicomponent mixtures of polyfunctional polyelectrolytes such as humic substances is well-known to be difficult due to the preponderance of separation mechanisms other than size exclusion (e.g., electrostatic and molecular interactions with the stationary phase). At this time, after years of application of SEC to humic materials, optimal elution and detection systems, as well as molecular size interpretations of chromatograms, are still quite controversial (Chin et al, 1994;Peuravuori and Pihlaja, 1997;Perminova et al, 1998;DeNobili and Chen 1999;Perminova 1999;Piccolo et al 1999;Kudryavtsev et al 2000;Perminova et al, 2003;Peuravuori and Pihlaja, 2004) etc. A recent study by Samburova et al (2005a) of WSOC extracted from urban aerosol from Zurich exemplifies this difficulty, displaying differences in estimated molecular size by nearly an order of magnitude as a function of the polymer standard applied.…”
Section: Size Exclusion Chromatography (Sec)mentioning
confidence: 99%
“…SEC characterization of complex multicomponent mixtures of polyfunctional polyelectrolytes such as humic substances is well-known to be difficult due to the preponderance of separation mechanisms other than size exclusion (e.g., electrostatic and molecular interactions with the stationary phase). At this time, after years of application of SEC to humic materials, optimal elution and detection systems, as well as molecular size interpretations of chromatograms, are still quite controversial (Chin et al, 1994;Peuravuori and Pihlaja, 1997;Perminova et al, 1998;DeNobili and Chen 1999;Perminova 1999;Piccolo et al 1999;Kudryavtsev et al 2000;Perminova et al, 2003;Peuravuori and Pihlaja, 2004) etc. A recent study by Samburova et al (2005a) of WSOC extracted from urban aerosol from Zurich exemplifies this difficulty, displaying differences in estimated molecular size by nearly an order of magnitude as a function of the polymer standard applied.…”
Section: Size Exclusion Chromatography (Sec)mentioning
confidence: 99%
“…Several authors have analyzed this class of compounds, mainly using size exclusion chromatography methods (SEC) (Fuzzi and Zappoli, 1996;Zappoli et al, 1999;Krivácsy et al, 2000) or spectroscopic methods such as diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS), UV or fluorescence spectroscopy (Havers et al, 1998;Zappoli et al, 1999;Kiss et al, 2003). SEC is also a widely used and well established technique in the field of humic and fulvic acid analysis (Rausa et al, 1991;Piccolo et al, 2001;Perminova et al, 2003;Janos, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Chromatographic analyses showed that the molecular weight of humic substances is primarily affected by their source (freshwater, soil, peat and coal). The maximum molecular weight and polydispersity values were observed for peat humic and fulvic acid, and soil humic acid (Perminova et al, 2003).…”
Section: Organic Substancesmentioning
confidence: 97%
“…During humification stable humic substances are formed by microbial transformation of non-humic substances (Table 1) such as hemicellulose, cellulose, lignin, pectins, bitumens, waxes, resins, nitrogenous materials, lipids, amino acids, non-saturated and saturated fatty acids, organic sulphur, various types of carbohydrates, starch compounds, ethereal oils, balsam, bioterin and tannic acid (Andriesse, 1988;Hruska, 1988;Riede et al, 1992;Banaszkiewicz and Drobnik, 1994;Anonym, 2002). Humic substances (Table 2) such as humic, fulvic, ulmic acids, and humins are the major part of humified peat (Hruska, 1988;Hruska, 1999;Anonym, 2002;Kocabagli et al, 2002;Janos, 2003;Perminova et al, 2003). They constitute a dark brown non-soluble fraction of peat with an extremely high molecular weight, responsible for the capability to retain water, friability and electrostatic conductivity.…”
Section: Organic Substancesmentioning
confidence: 99%